2014
DOI: 10.2118/169812-pa
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Hydraulic Performance of Drill Bits Using a Computational Particle-Tracking Method

Abstract: The hydraulic performance of fixed-cutter drill bits was studied with the ANSYS-FLUENT code (ANSYS 2012). Cuttings were modeled as spherical particles that were injected from the bottom of the hole, and discrete particle modeling (DPM) was used to track the cuttings in which particle/particle interaction is ignored. The ratio of average particle velocity to average annulus fluid velocity, referred to as the cuttings-transport ratio (C t ), was then evaluated to study the hydraulic performance of drill bits und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The whole calculation area is discretized by structured grid, and the boundary layer grid is divided at the solid wall. In view of the bottom hole submerged jet environment, the length of the calculation domain is usually set to 5 times of its width, which can ensure the full development of the bottom hole flow field, not only can meet the requirements of calculation accuracy [8], but also can save the calculation cost and greatly improve the model calculation efficiency.…”
Section: Calculation Area Establishmentmentioning
confidence: 99%
“…The whole calculation area is discretized by structured grid, and the boundary layer grid is divided at the solid wall. In view of the bottom hole submerged jet environment, the length of the calculation domain is usually set to 5 times of its width, which can ensure the full development of the bottom hole flow field, not only can meet the requirements of calculation accuracy [8], but also can save the calculation cost and greatly improve the model calculation efficiency.…”
Section: Calculation Area Establishmentmentioning
confidence: 99%
“…Taking advantage of the various applications of the Euler-Lagrange approach, many studies have been conducted, such as the evaluation of the deposition of pharmaceutical aerosols in human airways under different respiratory conditions [1], the design modification of cyclone separators [2], the insertion of a twisted tape to reduce elbow erosion [3], and the evaluation of the hydraulic performance of fixed cutter drill bits [4]. Another advantage is providing full information on particle trajectories and predicting differences in local particles' velocities, particle-particle collisions, and particle-wall interactions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mezhericher et al [20] used Fluent DPM methods to track particle trajectories; the calculation results revealed that the DPM method was more suitable for the simulation of flow fields whose particle volume fraction was below 10%, and the mixed fluid with this concentration ratio was also suitable for AWJ rust removal. Moslemi et al [21] studied the hydraulic characteristic of drill bits by Ansys Fluent software and applied DPM to track the cuttings. The simulation results indicated that the DPM method was more suitable for the prediction of hydraulic characteristics of liquid particle two-phase mixed fluid considering the interaction of the solid-liquid two phases.…”
Section: Introductionmentioning
confidence: 99%